Diffusivity of alcohols in amorphous polystyrene - Bernardo, Gabriel (2013)
Gravimetry is used to study the diffusion of a homologous series of alcohols (Cn, with n = 1, 2, 3, 4, 6, 10, and 16) in amorphous polystyrene at temperatures from 35 to 145 C, that is both below and above the polymer glass transition temperature of 100 C. All the mass uptake results are well described by a simple Fickian model (for t < t1/2) and are used to calculate the corresponding diffusion coefficients using the thin-film approximation. At any particular temperature, the alcohols Cn with n = 3, 4, and 6 possess very similar diffusivities despite the fact that the chain length doubles from C3 to C6. This peculiar diffusivity behavior is explained based on the variation of the polymer–solvent chemical affinity along the homologous series. As expected, at any particular temperature, the diffusivity decreases considerably from C6 to C10 and from C10 to C16. For each alcohol, its log(D) increases linearly with the decrease in liquid viscosity associated with an increase in temperature.